Search for Anomalous Quartic ZZγγ Couplings in Photon-Photon Collisions - M. Köksal; V. Arı; A. Senol (Advances in High Energy Physics)
The self-couplings of the electroweak gauge bosons are completely specified by the non-Abelian gauge nature of the Standard Model (SM). The direct study of these couplings provides a significant opportunity to test the validity of the SM and the existence of new physics beyond the SM up to the high energy scale. For this reason, we investigate the potential of the processes γγ→ZZ, e-γ→e-γ⁎γ→e-ZZ,  and e+e-→e+γ⁎γ⁎e-→e+ZZe- to examine the anomalous quartic couplings of ZZγγ vertex at the Compact Linear Collider (CLIC) with center-of-mass energy 3 TeV. We calculate 95% confidence level sensitivities on the dimension-8 parameters with various values of the integrated luminosity. We show that the best bounds on the anomalous fM2/Λ4, fM3/Λ4, fT0/Λ4, and fT9/Λ4 couplings arising from γγ→ZZ process among those three processes at center-of-mass energy of 3 TeV and integrated luminosity of Lint=2000 fb−1 are found to be [-3.30;3.30]×10-3 TeV−4, [-1.20;1.20]×10-2 TeV−4, [-3.40;3.40]×10-3 TeV−4, and [-1.80;1.80]×10-3 TeV−4, respectively.